Clinical Features of COVID-19 in Children - Zümrüt Şahbudak Bal; Zafer Kurugöl; Ferda Özkınay (Galenos Yayinevi, 2020)
In early December, pneumonia cases of unknown origin started to appear and, on the 7th of January 2020, these cases were declared to be caused by a novel beta-coronavirus according to viral genome sequencing on the 11th of February, 2020. Coronaviruses are enveloped, single strand RNA viruses that have been known to have the ability to mutate rapidly, alter tissue tropism and adjust to different epidemiological situations. As of the end of April 2020, 122,392 laboratory-confirmed cases of COVID-19 had been detected in Turkey, of whom 3,258 died. From the beginning of the COVID-19 epidemic, children seem to be less affected than adults. Therefore, there are limited data regarding the clinical features of COVID-19 in children. The majority of children with confirmed COVID-19 had a history of household contact. The most common symptoms were fever and cough. Previous data suggest that nearly half of patients are afebrile at the onset of the disease. Hospitalization and PICU admission rates for children were lower than for adults. However, PICU admission can be necessitated in children with severe disease. Infants, particularly under the age of 12 months, were more likely to develop severe disease. In children, milder and asymptomatic cases can be challenging and can play a role in transmission. In particular, clinicians should test those children who have a history of family cluster even though they are asymptomatic or present with mild symptoms.